The Effect of Magnetic Susceptibility on The Motion of Particles in A Ferrohydrostatic Separator. (2002) - Murariu, V.; Svoboda, J.
Abstract : Separation in magnetic fluids is a sink-and-float technique based on the generalised Archimedes law whereby, in addition to the conventional force of gravity, a magnetically induced force acts on the fluid. Since this density-based process takes place in a nonuniform magnetic field, magnetic properties of the material to be separated also play a role. The objective of this study is to derive an equation of motion of a non-magnetic particle in a magnetised magnetic fluid and to solve this equation analytically so that particle trajectories could be derived. Furthermore, the magnetic susceptibility of magnetisable particles is taken into account by means of the effective density of the particle. This effective density is the sum of the physical (true) density of the particle and the density associated with the interaction of the particle with the external non-homogeneous magnetic field. A criterion for the accuracy of separation in the form of threshold mass magnetic susceptibility is obtained. This criterion is then verified experimentally.